THE CHARACTERISTICS OF USING PROVERBS IN ORAL SPEECH - Uktamova Mokhigul Khamidullaevna; Mirzaahmedov Mirjalol Mansurjon ugli (Galaxy International Interdisciplinary Research Journal, 2023)
Text stylistics can be viewed as an area of study which deals with the interaction of the key factor of stylistic analysis such as author and the reader and the styles of the textual works. This article is devoted to the stylistics and its subgroup text stylistics, which provides the object the latter and the usage of stylistic analysis of texts in linguistics.